Enhancing Reinforced Concrete Beams: Investigating Steel Dust as a Cement Substitute - Ali Jahami; Hussein Younes; Jamal Khatib (Infrastructures, 2023)
This research undertook an extensive examination of the ramifications of integrating steel dust as a partial substitute for cement within reinforced concrete beams. The investigation encompassed an assessment of various facets, encompassing the workability of the concrete mixture, alongside crucial mechanical properties such as compressive strength, split tensile strength, flexural strength, ultrasonic pulse velocity (UPV), and elasticity modulus. The findings unveiled a notable reduction in workability as the proportion of steel dust increased within the mixture, with a consequential substantial impact on the elasticity modulus. Notably, compressive strength exhibited an enhancement at a 10% replacement of cement yet exhibited a decline with higher degrees of cement substitution. The inclusion of steel dust led to the formulation of adjusted equations pertaining to split tensile and flexural strength characteristics within the mixture. Remarkably, the incorporation of 10% steel dust yielded an increase in ductility. Conversely, at a 30% steel dust inclusion level, ductility diminished alongside a reduction in the maximum load-bearing capacity. In light of these findings, it is imperative to exercise prudence when considering the utilization of steel dust as a cement substitute, particularly when approaching or exceeding the 10% replacement level threshold. Further comprehensive research is imperative to acquire a comprehensive understanding of its implications and its susceptibility to potential corrosion concerns.